Comparative Analysis on Different parameters of Encryption Algorithms for Information Security - Mushtaque, Md Asif (International Journal of Computer Sciences and Engineering, 2014)
In this era information security is a very important issue in every field such as Government Agencies (CBI, FBI), Research Organization, E-commerce and etc. where internet is being used. We want to secure our data from unauthorized user. Cryptography is a technique to secure data on the network from unauthorized user. There are different types of a cryptography algorithm (a) symmetric and (b) asymmetric has been designed. To secure data it is necessary to know which algorithm provides better security, efficiency, accuracy and effectiveness. This paper presents the complete analysis of various symmetric key encryption algorithms (DES, 3DES, CAST-128, MARS, IDEA, Blowfish, AES, and RC6) based on different parameters such as: Architecture, Scalability, Security, Flexibility, and limitations.